Pendampingan Kelompok Program Kampung Iklim (Proklim) Temayang di Kecamatan Montong Gading Kabupaten Lombok Timur - Putra, Agus Muliadi; Haerudin, Haerudin; Darmawan, Muhammad Iman; Widiyanti, Baiq Liana; Hartini, Husnayati; Susanti, Dwi Rahayu; Septarini, Shofwatunnida’ (Universitas Hamzanwadi, 2023)
Climate change is an environmental phenomenon that poses various threats to human life. Various efforts have been made by the government to prevent the impacts of climate change, including by establishing the Climate Village Program (ProKlim). Community participation and collaboration is one of the important indicators in supporting the successful implementation of Proklim. Proklim Temayang is one of the Proklim groups in Montong Betok Village, Montong Gading District, which is currently proposing to level up to the main level. In order to carry out the preparation and data collection, cooperation was carried out in terms of group assistance with academics from the Environmental Engineering Study Program, Faculty of Engineering, Hamzanwadi University. Some of the activities carried out during the group's assistance were training and website development, making profile videos, and assisting in surveying and collecting regional spectrum data. The data covered are all data related to climate change adaptation and mitigation actions. The general and technical data were then inputted into the national registry system (SRN) through the spectrum application guided by personnel from the Bali Nusra Regional Directorate General of Climate Change Control (PPI). The last stage is the visitation process to verify the actual data and facts by the authorized party to be awarded